DEVELOPMENT OF THREE DIMENSIONAL DYNAMITE BOX FOOD NETS FOR THREE DIMENSIONAL LEARNING VIDEO MEDIA CLASS V SD NEGERI 060870 MEDAN TIMUR - Tambunan Husna Parluhutan (RADJA PUBLIKA, 2022)
This study aims to determine the development, feasibility and practicality of 3-dimensional learning video media for class V SD Negeri 060870 Medan Timur. This type of research is research and development using the ADDIE model. The instruments used are material expert validation sheets, media experts and student response questionnaires. The results of research related to feasibility show that at this stage the researcher evaluates the media that has been developed based on the results of the media feasibility assessment by material experts, media experts, and classroom teachers. Judging from the validators of material experts, media experts, and classroom teachers, the average assessment was %, 92%, 91.4%. Based on the results of the validation of Animaker-based animation learning media, it is in the